Legal Protection for Children Perpetrating the Crime of Theft Based on Restorative Justice - Hidayat, Sarip; Adhyakhsa, Gios; Rifa'i, Iman Jalaludin; Hermansyah, Dadan (Fakultas Hukum, Universitas Islam Bandung, 2024)
Arrangement opposite child with law as perpetrator follows criminal arranged in Constitution Number 12 of 2011 concerning System Justice Juvenile Crime which is umbrella law on protection against child with law until this moment, form and procedure implementation crime and Action against child arranged in Government Regulation Number 58 of 2022, This is a mandate from Article 71 paragraph (5) and Article 82 paragraph (4) of Constitution Number 12 of 2011 concerning the Child Crime Justice System. The research method used in this study is a normative juridical method with regulatory primary data applicable laws and secondary data books, reports, journals and interviews on parties related as primary data amplifier. Research results This is The goals of the juvenile justice system is For repairs behaviour child And give education as well as protection that the child needs , so the child when returning to environmental society can be accepted easily and can operate Again functions child, there is accompaniment law in the judicial process these and rights fulfillment child Already in accordance with applicable laws. Settlement process in a manner justice restorative and Diversion ie form mandatory solution attempted to oppose child with law Good as perpetrator following criminal, victim of criminal crime or witness following crime, then in the process of investigation party investigator must make an effort settlement in a manner restorative justice and Diversion, as well should be when prosecuted general as well as in mandatory Diversion courts attempted to child, in Diversion should be There is agreement between the parties for the resolution process in accordance with what is desired and obtain a sense of justice to child.